How is The Development of Valid and Practical Android-Based Local Wisdom Teaching Materials? - I Made Mudiartana; I Gede Margunayasa; Dewa Gede Hendra Divayana (Jurnal Ilmiah Sekolah Dasar, 2021)
The Covid-19 pandemic has caused the learning process to shift from face-to-face to virtual. This research aimed to produce android-based local wisdom digital teaching materials for grade V of valid and practical elementary schools. This research was a research development (R&D) with ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The subject of this research was android-based digital teaching materials with local wisdom. In contrast, the research object was the validity and practicality of android-based digital teaching materials with local wisdom. The data in this study were classified into two qualitative and quantitative data. Data collection techniques were using questionnaire techniques. The questionnaires are used to measure the validity and practicality of digital teaching materials. The validity was tested by two experts, namely material experts and media experts. The practicality of digital teaching materials was assessed by five teachers and ten grade V elementary school students in the Letda Kajeng Cluster. The data collected was then analyzed descriptively quantitatively. The results of this study indicate that (1) the validity of android-based digital teaching materials with local wisdom obtained an average of 3,64 or is in the interval of 3,50 ≤ Rv ≤ 4,00 with the criteria "very valid"; (2) the practicality of digital teaching materials with local wisdom based on the teacher's and student assessment obtained an average of 3,67 which is in the interval of 3,50 ≤ Rk ≤ 4,00 with the category "very practical". Based on the study results, it was concluded that this development research produced Android-based digital teaching materials with local wisdom on Panas dan Perpindahannya topics for grade V elementary school, which were very valid and very practical.